Acute effects of oral mesna administration on the full amino acid profile and 3-methylhistidine: secondary results from the CYLOB dose-finding study - Olsen, Thomas; Elshorbagy, Amany; Stolt, Emma; Åsberg, Anders; Zaré, Hasse K.; Bastani, Nasser E.; Refsum, Helga; Retterstøl, Kjetil; Vinknes, Kathrine J. (Amino acids, 2024)
Plasma total cysteine (tCys) is strongly associated with fat mass in humans. Mesna lowers plasma tCys in a dose-dependent manner, but it is not known whether it interferes with metabolism of other amino acids or protein. In this Phase-1 study, we show that a single dose of mesna administered at 400, 800, 1200 or 1600 mg to 6–7 individuals per dose only slightly affects amino acid profiles, with increases in plasma valine across dose levels. There were no effects of mesna on 3-methylhistidine, a marker of protein breakdown.